Diptych on the “Ecological” Home of Being — Before and Today - Bajor, Wanda (Roczniki Kulturoznawcze, 2023)
One of the manifestations of the contemporary cultural and civilizational crisis is the ecological crisis caused by the overexploitation and devastation of the natural living environment. The root cause of this phenomenon is seen in false thinking and a narrowed cognitive perspective directed exclusively towards utilitarian processing of the world and the reduction of man as a means in the pursuit of economic gain. Already at the beginning of the 20th century, existentialists such as Martin Heidegger and Gabriel Marcel, as well as contemporary Joseph Ratzinger, warned of these dangers, postulating a return to such ideas as integral knowledge of man, God and the world directed towards wisdom, contemplation, fraternity, humility and asceticism in the sense of modesty of intention. These are not some new ideas invented for the moment; they are all to be found in the ancient heritage of European culture, especially in the forgotten, despised Middle Ages, whose wisdom and rich deposits of meaning still remain undiscovered. The works of the medieval masters containing unsurpassed syntheses of knowledge about the whole of reality, the beauty of the natural world, human dignity, the meaning of life and its ultimate goals can inspire, teach and nourish today's lost, spiritually starved man.